Effects of Morinda citrifolia on growth performance and health of high-risk calves - L.R. Hibbard; R.G. Godbee; M.P. Epp; Brandon E. Oleen; Dale A. Blasi; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 2010)
Bovine respiratory disease continues to be the most costly disease affecting productivity and profitability in the stocker segment. Long-acting injectable antimicrobials are presently used to reduce the incidence and severity of bovine respiratory disease. However, future use of antimicrobial treatment may be significantly curtailed in light of an increasing negative perception of antibiotic usage in food animals by consumers and governmental agencies. Consequently, preconditioning and enhanced nutrition programs that may include nutraceuticals could become more prevalent. MorindaMax (Morinda International, Provo, UT) is a natural product manufactured from the Morinda citrifolia fruit (i.e., Noni). Published literature suggests this plant extract has a broad range of immune-enhancing effects, including antibacterial, anti-inflammatory, analgesic, antioxidant, and anti-tumor effects.
Keywords: Cattlemen& #x27; s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen& #x27; s Day; Beef; Growth; Performance; Bovine respiratory disease